On the Specificity of Religion (Notes on the Origin of the Religion of Ancient Lithuanians) - Trinkūnas, Jonas (Problemos, 1973)
The paper deals with the late origin of the religious conception of the world which was preceded by the mythological one. The author analyses the conditions of the origin of religion and shows the development of religion under concrete conditions of the pre-Christian Lithuania. The paper presents a general picture of the relationship of the ancient Lithuanian religion with the mythology and the official Christian religion.